DAMPAK KRISIS KEUANGAN GLOBAL TERHADAP PERBANKAN DI INDONESIA: Perbandingan antara Bank Konvensional dan Bank Syariah - M. Zidny Nafi’ Hasbi (LP2M Universitas Ibrahimy, 2019)
This article analyzes the impact of global financial crisis to Indonesian banking condition, a comparison between shari’ah and conventional bank. It starts with description about the root of financial crisis and its impact to Indonesian financial sector. Both shari’ah and conventional bank face the effects of the crisis and react to Bank Indonesia policy. As Bank Indonesia raises BI rate, conventional bank increases its interest as response to policy which mean businessmen have to pay higher for money they borrow from bank. Such a condition makes businessmen move to shari’ah bank in which its profit and losing share financing system make them pay the same amount as they borrow. The article concludes that sharia banking is stronger than conventional bank in facing financial crisis.